2019
DOI: 10.1111/jpm.12572
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with the evolution of attitudes towards mental illness in a cohort of nursing students

Abstract: Accessible SummaryWhat is known on the subject? People with mental health difficulties have poorer physical health than the general population. The stigmatizing attitude of health professionals impacts the quality of care for these people. There is a broad background on the effectiveness of activities based on theoretical training, clinical practices or social contact to improve nursing students’ attitudes towards people with mental health difficulties. There is an important need to assess whether the bene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 67 publications
0
10
0
Order By: Relevance
“…Although the conclusions of O'Ferrall‐González et al (2020) are not borne out by other studies, several authors report that nursing students feel closer to people with MHPs and express acceptance and positive attitudes toward them (Çingöl et al, 2019; Granados‐Gámez et al, 2017). However, in our study, specific clinical training in mental health in the group of students with an MHP may have aroused a process of avoidance or silencing of their own personal situation.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Although the conclusions of O'Ferrall‐González et al (2020) are not borne out by other studies, several authors report that nursing students feel closer to people with MHPs and express acceptance and positive attitudes toward them (Çingöl et al, 2019; Granados‐Gámez et al, 2017). However, in our study, specific clinical training in mental health in the group of students with an MHP may have aroused a process of avoidance or silencing of their own personal situation.…”
Section: Discussionmentioning
confidence: 95%
“…In both cases, this association was unaffected by social desirability (Çingöl et al, 2020), in contrast, concluded that at the end of the training period, nursing students who presented MHP or were close to someone with MHP displayed positive attitudes toward mental health issues: similar results were reported in students with more advanced knowledge and skills in mental health after training that included direct contact with people with MHP (Sayols‐Villanueva et al, 2015). O'Ferrall‐González et al (2020), on the other hand, found that the positive attitudes identified during the theoretical training did not last over time, and that by the end of their clinical placements the attitudes of some nursing students toward MHP had worsened. For these authors, then, familiarity with MHP was not a predictor of positive attitudes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One possible explanation is that those differences are due to age/generation effects. Another possible explanation for the stigmatization of schizophrenia among nursing students is the students’ experiences of the emotional distress or disturbing behaviors exhibited by people with schizophrenia [ 26 ]. Notably, the fourth-year students have already completed both classroom education and a clinical internship on psychiatry.…”
Section: Discussionmentioning
confidence: 99%
“…An important aspect of students’ first experiences as professional nurses is learning to manage emotionally distressing situations [ 25 ]. Added to this is the pressure of being evaluated [ 26 , 27 , 28 ]. Although the dimension “contact with human suffering” did not show significant differences, we observed high stress scores in relation to the rest of the dimensions.…”
Section: Discussionmentioning
confidence: 99%